Implementasi Model Pembelajaran Creative Problem Solving (CPS) Untuk Meningkatkan Kemampuan Pemecahan Masalah Mahasiswa - Satriani, Sri; Wahyuddin, Wahyuddin (Pendidikan Matematika Universitas PGRI Yogyakarta, 2018)
This study aimed to improve studentsâ€™ problem-solving skills and to describe the implementation of creative problem solving (CPS) model in Mathematics Education students of the Muhammadiyah University of Makassar in its program. This research was a classroom action research which involved 33 students with two cycles (1 cycle was 4 times meeting). The cycling stage consisted of planning, action, observation, reflection. Data collection through observation, test result, and student response were analyzed by quantitative descriptive analysis technique. The research finding was: Implementation of learning model (CPS) can improve studentsâ€™ problem-solving ability which can be seen from the increasing of solving ability from 63,03 (enough) to 77,72 (high). Effective learning (CPS) implementation with learning implementation indicators improved from less category to excellent category; student activeness increased from active category to highly active category, and student responses were in a very positive category. (2) Implementation of Learning Model (CPS) can be implemented through five stages: clarification of the problem; disclosure of ideas; evaluation; and implementation.Â Keyword: Learning Model, Creative Problem Solving (CPS), and Problem Solving Ability.